2022
DOI: 10.3390/informatics9020047
|View full text |Cite
|
Sign up to set email alerts
|

An Interoperable Electronic Health Record System for Clinical Cardiology

Abstract: Currently in hospitals, there are several separate information systems that manage, very often autonomously, the patient’s personal, clinical and diagnostic data. An electronic health record system has been specifically developed for a cardiology ward and it has been designed “ab initio” to be fully integrated into the hospital information system and to exchange data with the regional health information infrastructure. All documents have been given as Health Level 7 (HL7) clinical document architecture and mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In 2017, the MII National Steering Committee produced a first document, later updated, containing a high-level description of the CDS as well as recommendations on the syntactic and semantic standards to be employed in all modules 7 . On the structural level, information should be modeled using the Fast Healthcare Interoperability Resources (FHIR) 8 , a recent Health Level Seven (HL7) 9 standard rapidly gaining adoption for the exchange of healthcare information 10 12 . It is organized in several resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the MII National Steering Committee produced a first document, later updated, containing a high-level description of the CDS as well as recommendations on the syntactic and semantic standards to be employed in all modules 7 . On the structural level, information should be modeled using the Fast Healthcare Interoperability Resources (FHIR) 8 , a recent Health Level Seven (HL7) 9 standard rapidly gaining adoption for the exchange of healthcare information 10 12 . It is organized in several resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In personalized medicine, it is essential to accurately describe the situation of a patient at all levels (from macroscopic [25] to molecular [26]) [27,28]. This kind of systems combines on the one hand the analytical nature of ontologies and on the other hand the systematic approach and rigor provided by standardized tools, such as the CTS2, to preserve the evolutionary history of the terminological systems.…”
Section: Discussionmentioning
confidence: 99%
“…An informal study on the implemented system's effectiveness in two hospitals showed that EHRs improved patient management. Moreover, the software supporting HDL preparation, that is, the document summarising the hospitalisation and including indications for continuing treatment, was found to be the most appreciated functionality [63]. Other positive effects that translated into increasing engagement with the system were an increase in the usability of the base, with studies noting, among other things, increased prescription appropriateness, a reduction in overall nurse workload, and optimisation of medication inventory management.…”
Section: Case #3: Electronic Medical Record In Italian Academic Integ...mentioning
confidence: 99%